MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR SISWA DALAM ANSAMBEL MUSIK MELALUI METODE TUTOR SEBAYA PADA SISWA KELAS VIII B SMP NEGERI 1 MOGA PEMALANG - Haryanto, Haryanto (Universitas Negeri Semarang, 2014)
The purpose of this study is to determine (1) the improvementof students achievement in the subjects of Arts and Culture, specifically the basic skills competencies to play music ensemble, and (2) the improvement of students learning activities in the subjects of art and culture, particularly the basic competency skills of playing music ensemble. The method used is this research is classroom action research by using peer tutoring which includes four stages: (1) planning, (2) implementation, (3) observation, (4) analysis and reflection. The research design used in this research was applied research design according Chemish Tagart. This research is collaborative, involving cultural arts teachers to carry out the observation and reflection. Results were analyzed by quantitative descriptive techniques to describe the data and compare the findings with predetermined performance indicators. The results of this study indicate that: First, peer tutoring learning can improve students achievement at Moga Junior High School 1. This is proven by the material mastery improvement from 36.11% on the pre-cycle to 83.33% by the end of the second cycle. Second, peer tutoring method can improve students learning activity. This is proven by the improvement in activity score from 2.30 on the pre cycle activity to 3.51 by the end of the second cycle. Peer tutoring learning methods should be developed in schools teaching materials, especially music ensemble which requires a long time allocation to practice the skills of playing music.